Dehydration as a Rare Cause of Pulmonary Artery Thrombosis in a 2-Week-Old Term Neonate - Kimhi, Gal; Rubinshtein, Marina; Tirosh-Wagner, Tal; Mishaly, David; Kenet, Gili; Paret, Gideon (Journal of Pediatric Intensive Care, 2018)
Pulmonary arterial thrombosis is an extremely rare occurrence in the neonatal population. We describe a 2-week-old female neonate who presented in critical condition with severe cyanosis and dehydration and was found to have a large thrombus in the main branches of the pulmonary arteries. She was successfully treated with surgical embolectomy. Pulmonary arterial thrombosis should always be considered in the differential diagnosis of a dehydrated neonate presenting with severe cyanosis and evidence of pulmonary hypertension.
Keywords: pulmonary arterial thrombosis; neonate; dehydration; cyanosis; pulmonary hypertension